Румунія і Молдова: дві країни, одна нація - Кульчицький, С. (Регіональна історія України, 2013)
In 1812 Russia regained from the Ottoman Empire the territory of the province of Bessarabia. Its central part was the ethnic territory of the principality of Moldavia. Halfway through the century Wallachia and Moldavia (Moldova) established the new state – Romania. At the end of the 20th century the Republic of Moldova emerged on the basis of two-thirds of Bessarabia and Transnistria, the region that formerly belonged to Ukraine. This article analyzes the policies of Russian, Ukrainian, Romanian and Moldavian governments concerning Bessarabia problem.